Provision of Strategic Directional Signs (PANTERAS) as Environmental Information Media in RT 29 RW 01, Pematang Gubernur Village - Muhammad Mallik Rondesha; Andini Risha Septiani; Meksi Despa; Doni Pratama; Lydia Gustina Putri; Hesti Nur'aini; Liza Yulianti (Jurnal Pengabdian Mandiri, 2026)
Pematang Gubernur Subdistrict is a residential area with relatively high population density and diverse community activities. However, limited directional information signs are still found in RT 29 RW 01, particularly regarding public facilities and strategic locations. This condition makes it difficult for visitors and newcomers to navigate the area. This community service program aims to provide environmental information media through the creation and installation of Strategic Direction Signboards (PANTERAS). The implementation methods include field observation, signboard design, construction, installation at strategic points, and brief socialization to residents. The results show that the signboards help improve environmental order and facilitate access to location information for the community.